The development and nutritional quality of Lyophyllum decastes affected by monochromatic or mixed light provided by light-emitting diode - Chen, Xiaoli; Liu, Yihan; Guo, Wenzhong; Wang, Mingfei; Zhao, Jiuxiao; Zhang, Xin; Zheng, Wengang (Frontiers in Nutrition, 2024)
Edible fungi has certain photo-sensitivity during the mushroom emergence stage, but there has been few relevant studies on the responses of Lyophyllum decastes to different light quality. L. decastes were planted in growth chambers with different light qualities that were respectively white light (CK), monochromatic red light (R), monochromatic blue light (B), mixed red and blue light (RB), and the mixture of far-red and blue light (FrB). The photo-sensitivity of L. decastes was investigated by analyzing the growth characteristics, nutritional quality, extracellular enzymes as well as the light photoreceptor genes in mushroom exposed to different light treatments. The results showed that R led to mycelium degeneration, fungal skin inactivation and failure of primordial formation in L.. The stipe length, stipe diameter, pileus diameter and the weight of fruiting bodies exposed to RB significantly increased by 8.0%, 28.7%, 18.3% and 58.2% respectively, compared to the control (P<0.05). B significantly decreased the stipe length and the weight of fruiting body, with a decrease of 8.5% and 20.2% respectively, compared to the control (P<0.05). Increased color indicators and deepened simulated color were detected in L. decastes pileus treated with B and FrB in relative to the control. Meanwhile, the expression levels of blue photoreceptor genes such as WC-1, WC-2 and Cry-DASH were significantly up-regulated in mushroom exposed to B and FrB (P<0.05).Additionally, the contents of crude protein and crude polysaccharide in pileus treated with RB were respectively increased by 26.5% and 9.4% compared to the control, while those in stipes increased by 5.3% and 58.8% respectively. Meanwhile, the activities of extracellular enzyme such as cellulase, hemicellulase, laccase, manganese peroxidase, lignin peroxidase and amylase were significant upregulated in mushroom subjected to RB (P<0.05), which may promote the degradation of the culture materials. On the whole, the largest volume and weight as well as the highest contents of nutrients were all detected in L. decastes treated with RB. The study provided a theoretical basis for the regulation of light environment in the industrial production of high quality L. decastes.